Geochemical atlas of Europe: Background information, methodology and maps. - Salminen, R (Geological Survey of Finland / Finland, 2005)
The IUGS/IAGC Global Geochemical Baseline Programme aims to establish a global geochemical reference baseline for >60 determints in a range of media for environmental and other applications. The European contribution to the programme has been carried out by government institutions from 26 countries under the auspices of the Forum of European Geological Surveys (FOREGS). The main objectives of this European survey were: 1) to applay standardised methods of sampling, chemicval analysis and data managment to prepare a geochemical baseline across Europe ; and 2) to use this reference network to level national baseline datasets. Samples of stream water, stream sediment and three types of soil (organic top layer, minerogenic top and sub soil) have been collected at 900 stations, each representing a catchment area of 100 km2, corresponding to a sampling density of about one sample per 4700 km2. In addition, the uppermost 25 cm of floodplain sediment was sampled from 790 sites each representing a catchment area of 1000 km2. All soil and sediment samples were prepared at the same laboratory, and all samples of particular sample types were analysed by the same method at the same laboratory. More than 50 elements, both total and aqua regia extractable concentrations, and other parameters (such pH and grain size) were determined on the <2 mm grain size fraction of soil and floodplain sediment samples and on the <0.15 mm grain size fraction of stream sediment samples, and total concentrations of organic soil samples were measured after using a strong acid digestion. Nine laboratories of European geological surveys carried out the analytical work. Altogether, 360 geochemical maps showing the distribution of elements across Europe have been prepared. All the results and field observations are organised in a common database and the maps are published as a Geochemical Atlas of Europe. All the sampling sites were photographed and this photo archive is also available. Samples have been archived in the Slovak Republic for possible future use. Initial results show that the distribution patterns of both water and solid samples are related to such factors as large-scale tectonic provinces, geochemical variations of large lithological units, extension of the Weichselian glaciation, and contamination reflecting industrialized areas and regions of intensive agriculture.